UNESCO project «National school-laboratory on bioethics for schoolchildren – instrument of implementing the Agenda 2030 in the Republic of Belarus» - Goncharova, Nadezhda V. (Journal of the Belarusian State University. Ecology, 2020)
The author assesses the significance of UNESCO’s bioethics programs, various methods and aspects of its application, and its role in environmental education. The principal statements of the UNESCO project carried out at the International Sakharov Environmental Institute Belarusian State University are reviewed. The Basic principles of environmental education such as continuity, gradualness, stages of personality formation and their implementation in the education process are discussed.
Keywords: UNESCO; bioethics; innovative technologies; environmental education